Brilliant self confidence : how to challenge your fears and go for anything you want in life - McClement, Mike (Pearson, 2012)
Everyone can build lasting, unshakable confidence and go after the life they really want to live. Whether it's making a career change, finding a romantic partner or meeting new people, Brilliant Self-confidence is packed with all the advice necessary to help you develop the confidence and motivation to be successful, so you can change your approach to life forever and start transforming your life today. BRILLIANT OUTCOMES Feel motivated, positive and confident Learn to exploit your strengths and embrace opportunities Find out how to overcome setbacks Assert yourself and go after t.